Optimisme dalam Keterbatasan: Bimbingan Rohani Islam dalam Meningkatkan Kualitas Hidup Pasien dengan Diagnosis F06.8 - Maulida, Dzikrah; Sahera, Ghani Aurina; Faishol, Lutfi; Prihmaningrum, Vici (Assertive: Islamic Counseling Journal, 2024)
Patients with a diagnosis of F06.8 have problems such as feelings of hopelessness, social stigma, and difficulty in carrying out daily activities, which can have an impact on mental health. This study aims to determine the internalization of Islamic spiritual guidance to increase optimism and quality of life in patients diagnosed with F06.8. This research is a qualitative research type with a case study. The subject with the initials FA was diagnosed with mental disorder F06.8 at the Tirto Jiwo Rehabilitation Home. Data collection techniques using interviews, experiments, and observations with triangulation of sources from patient caretakers and patients. The research results show that Islamic spiritual guidance contributes to increasing optimism and quality of life in patients diagnosed with F06.8. Islamic spiritual guidance activities can strengthen emotional bonds but also create a positive environment so that patients feel more accepted and appreciated. Islamic spiritual guidance is an important aspect in supporting the patient's mental and emotional well-being.   Pasien dengan diagnosis F06.8 memiliki masalah seperti perasaan putus asa, stigma sosial, dan kesulitan dalam menjalani aktivitas sehari-hari yang dapat berdampak pada kesehatan mental. Penelitian ini bertujuan untuk mengetahui internalisasi bimbingan rohani Islam untuk meningkatkan optimisme dan kualitas hidup pada pasien dengan diagnosis F06.8. Penelitian ini merupakan penelitian kualitatif dengan jenis studi kasus, subjek berinisial FA dengan diagnosis gangguan mental F06.8 di Panti Rehabilitasi Tirto Jiwo. Teknik pengumpulan data dengan wawancara, eksperimen, serta observasi dengan triangulasi sumber dari penjaga pasien dan pasien. Hasil penelitian bahwa bimbingan rohani Islam memberikan kontribusi dalam meningkatkan optimisme dan kualitas hidup pasien dengan diagnosis F06.8. Kegiatan bimbingan Rohani Islam bisa memperkuat ikatan emosional, tetapi juga menciptakan lingkungan yang positif, sehingga pasien merasa lebih diterima dan dihargai. Bimbingan rohani Islam menjadi salah satu aspek penting dalam mendukung kesejahteraan mental dan emosional pasien.